The implementation of tax imposition Micro Small Medium Enterprise (MSME) in the form of limited companies after the expiry period of final income tax - Akbar, Lutfia Rizkyatul; Sugiarti, Rita (Educoretax, 2024)
The MSME tax policy has undergone several changes and changed regulations. In 2022, the government again re-regulated MSME taxes, namely PP Number 55 year 2022 regarding Adjustments to Regulations on Income Tax. This research uses a descriptive qualitative approach. With the issuance of PP Number 55 of 2022, this provides an opportunity to increase the taxes owed by MSMEs and researchers also want to illustrate to the government that after this regulation is issued what impact will be felt by MSME Taxpayers, so that this will later be used as an evaluation by the Government.  The result of this research is the calculation for the 2023 tax year using the rate of Article 17 of the Income Tax Law with the rate of 22%, and an additional 50% tax reduction as the Income Tax Law Art 31 E, resulting in the tax payable of IDR 4,240,946.16. PT ABC must carry out the bookkeeping obligations in reporting the tax liabilities and create proof of transactions for every business transaction to avoid a high tax burden.